1993
DOI: 10.1039/c39930000574
|View full text |Cite
|
Sign up to set email alerts
|

1,10-Diaza-4,7,13,16-tetraoxacyclooctadecane-1,10-bis(malonate), a ligand with high Sr2+/Ca2+and Pb2+/Zn2+selectivities in aqueous solution

Abstract: The stability constants of the complexes of 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-l ,I 0-bis(ma1onate) formed with alkaline-earths, lanthanides, zinc, cadmium and lead are larger for larger metal ions, which is manifested in unusually high Sr2+/Ca*+ and Pb2+/Zn2+ selectivities in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“… 33 Macropa was also found to selectively bind large lanthanide, 34 alkaline earth, 35 , 36 and p-block 35 metal ions over their smaller analogues. The selectivity for the large An and Ln ions was found to be superior to related diaza[18]crown-6 25 , 28 and diaza[15]crown-5 derivatives. 37 , 38 This rare reverse size selectivity of macropa makes it a distinguished candidate for medical applications, where efficient chelators for large metal ions are highly needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Macropa was also found to selectively bind large lanthanide, 34 alkaline earth, 35 , 36 and p-block 35 metal ions over their smaller analogues. The selectivity for the large An and Ln ions was found to be superior to related diaza[18]crown-6 25 , 28 and diaza[15]crown-5 derivatives. 37 , 38 This rare reverse size selectivity of macropa makes it a distinguished candidate for medical applications, where efficient chelators for large metal ions are highly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Macrocycles based on the 1,7,10,16-tetraoxa-4,13-diazacyclooctadecane (D18C6) core show a thermodynamic preference for large over small metal ions. Recently, a D18C6-based macrocycle possessing two picolinate arms ( N , N ′-bis­[(6-carboxy-2-pyridil)­methyl]-4,13-diaza-18-crown-6, macropa, Figure ) has been shown to form rapidly a stable complex with 225 Ac 3+ , the largest 3+ ion in the Periodic Table . Macropa was also found to selectively bind large lanthanide, alkaline earth, , and p-block metal ions over their smaller analogues.…”
Section: Introductionmentioning
confidence: 99%
“…In ongoing efforts to develop ligands that form stable complexes with large metal ions, we have investigated the coordination properties of macrocycles based on the 1,7,10,16-tetraoxa-4,13-diazacyclooctadecane (D18C6) core. , This 18-membered macrocycle (Chart ) gives rise to ligands that exhibit an unusual thermodynamic preference for large over small metal ions. As discussed above, this trend is in contrast to the majority of conventional poly­(aminocarboxylate) ligands that form more stable complexes with smaller ions. Notably, our studies have revealed that macropa (Chart ), a D18C6-based macrocycle possessing two picolinate pendent arms, can rapidly form a stable complex with 225 Ac 3+ , the largest 3+ ion in the Periodic Table .…”
Section: Introductionmentioning
confidence: 99%
“…As such, we reasoned that the investigation of chelators with a reverse size-selectivity, a preference for large over small ions, would be a promising direction for the development of new BFCs for this radionuclide. In this context, ligands containing the 18-membered diaza-18-crown-6 macrocycle display this reverse size-selective property for metal ions. Previously, we showed that macropa (Chart ) forms remarkably stable complexes with large medicinally relevant radiometals like 132/135 La, 223 Ra, and 225 Ac. ,, We further showed that alteration of the pendent donor arms and macrocyclic core rigidity changes the resulting selectivity for different metal ions. ,, On the basis of the reverse size-selectivity properties and tunability of this system, we sought to explore this class of ligands (Chart ) for chelating Bi 3+ for potential applications in TAT.…”
Section: Introductionmentioning
confidence: 99%